Preparação de nanopartículas de poli (metacrilato de metila) carregadas com filtros solares por processo mediado por membrana de vidro (SPG) - Salomão, Bruna Rodrigues (2016)
Ultraviolet radiation (UV) emitted by the sun can cause skin cancer. For this reason, it is important to prevent the damage of skin with the use of topical sunscreens, which are intended to block the penetration of radiation into the skin layers. Encapsulation of sunscreens into polymeric nanoparticles has constituted the subject of many scientific researches due to the lower dermal absorption of active compounds and higher solar protection factor. This work used glass membrane (SPG) for prepration of nanoemulsions of methyl methacrylate, avobenzone and octocrylene, which were polymerized throught radical miniemulsion polymerizations. The obtained nanoparticles presented narrower size distributions, when compared to those obtained through sonication. Finally, in vitro tests of solar protection factor showed that the obtained nanoparticles, containing the encapsulated active compounds and prepared with help of SPG membrane find potential for use in photoprotective formulations.